(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2023)
This research explores the dynamic and evolving landscape of European street art as a powerful medium for expressing socio-political issues. Street art has emerged as a significant form of public discourse, reflecting the voices of diverse communities and providing a platform for marginalized perspectives. Focusing on the European context, this study investigates how street artists engage with and represent socio-political issues through their creations. The research employs a multidisciplinary approach, drawing on art history, sociology, and cultural studies to analyze the visual, symbolic, and contextual dimensions of street art. By examining a diverse range of artworks from cities across Europe, the study aims to identify recurring themes, motifs, and techniques employed by street artists to convey socio-political messages. Themes may include but are not limited to activism, social justice, environmental concerns, identity politics, and responses to geopolitical events.